Elementary motor perseveration in early diagnosis of progressive supranuclear palsy - Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
Three patients with progressive supranuclear palsy (PSP) with different symptoms at onset presented intense elementary motor perseverations before the appearance of the distinctive features of the illness. In elementary motor perseveration once an element of a movement has begun it is no longer inhibited at the right time and continues unchecked. Perseverations were observed in these patients during tests for dysdiadokokinesia, for reproduction of rhythmic structures and during the drawing of simple geometric shapes. Though this sign has not yet been described in PSP it is possible that an adequate search for its occurrence may show it to be an important sign for early diagnosis and an element for the clinical characterization of PSP.